Low frequency power in cerebral blood flow is a biomarker of neurologic injury in the acute period after cardiac arrest. (September 2022) - White, Brian R.; Ko, Tiffany S.; Morgan, Ryan W.; Baker, Wesley B.; Benson, Emilie J.; Lafontant, Alec; Starr, Jonathan P.; Landis, William P.; Andersen, Kristen; Jahnavi, Jharna; Breimann, Jake; Delso, Nile; et al.
Abstract: Aim: Cardiac arrest often results in severe neurologic injury. Improving care for these patients is difficult as few noninvasive biomarkers exist that allow physicians to monitor neurologic health. The amount of low-frequency power (LFP, 0.01–0.1 Hz) in cerebral haemodynamics has been used in functional magnetic resonance imaging as a marker of neuronal activity. Our hypothesis was that increased LFP in cerebral blood flow (CBF) would be correlated with improvements in invasive measures of neurologic health. Methods: We adapted the use of LFP for to monitoring of CBF with diffuse correlation spectroscopy. We asked whether LFP (or other optical biomarkers) correlated with invasive microdialysis biomarkers (lactate-pyruvate ratio – LPR – and glycerol concentration) of neuronal injury in the 4 h after return of spontaneous circulation in a swine model of paediatric cardiac arrest ( Sus scrofa domestica, 8–11 kg, 51% female). Associations were tested using a mixed linear effects model. Results: We found that higher LFP was associated with higher LPR and higher glycerol concentration. No other biomarkers were associated with LPR; cerebral haemoglobin concentration, oxygen extraction fraction, and one EEG metric were associated with glycerol concentration. Conclusion: Contrary to expectations, higher LFP in CBF was correlated with worse invasive biomarkers. Higher LFP may represent higher neurologic activity, or disruptions in neurovascular coupling. Either effect may be harmful in the acute period after cardiac arrest. Thus, these results suggest our methodology holds promise for development of new, clinically relevant biomarkers than can guide resuscitation and post-resuscitation care. Institutional protocol number: 19-001327.